EVALUATION OF HIGH-QUALITY CASSAVA FLOUR WHEAT BREAD SPICED WITH CLOVE POWDER - Adetoro, Oluwatoyin Funke; Kajihausa, O. Esther; Sobukola, O. Philip; Afolabi, Wasiu Akinloye O. (FUDMA JOURNAL OF SCIENCES, 2025)
Clove is a novel food ingredient enriched with polyphenolic compounds. The utilization of clove powder for the production of bread dough could improves its processing condition and thereby enhances some of the quality attributes of the bread dough. This study investigated some quality attributes of wheat flour (WF) and High-Quality Cassava Flour (HQCF) spiced with clove powder (CP). Flour blends were produced from 90% WF and 10% HQCF with inclusion of clove powder at 0.10, 0.50, 1.00, 1.50 and 2.00% respectively. Bread samples were produced from the blends while 90% WF and 10% HQCF was used as control. Water absorption capacity [WAC], Functional properties (bulk density [BD], swelling power [SP], oil absorption capacity [OAC], solubility index [SI]) and pasting properties of flour blends as well as rheological properties in terms of farinograph water absorption (FWA), dough development time (DDT), dough stability time (DST), degree of dough softness (DDS) and farinograph quality number (FQN) of the flour dough were determined using standard procedures. Data were analysed using descriptive and inferential statistics. The values of functional properties are BD, WAC, OAC and SP ranged from 0.73 to 0.78 g/ml, 1.23 to 2.12 ml/g, 1.86 to 2.51 ml/g and 3.24 to 3.8 ml/g respectively while SI decreased from 10.45 to 9.11 ml/g. Pasting viscosities (RVU) such as peak (210.71-237.25), trough (118.04-151.38), final (199.33-236.38), setback (73.96-88), plus peak time (5.13-6.98 min) and pasting temperature (71.66-73.46 0C) decreased while breakdown viscosity (69.88-96.75) increased with CP addition. FWA (62.35-62.9%) increased while FQN (71.5-98.5 mm) decreased with...